2007
DOI: 10.1107/s0907444906052024
|View full text |Cite
|
Sign up to set email alerts
|

His-tag impact on structure

Abstract: Crystallographers are increasingly determining structures of protein constructs that include His tags. Many have taken for granted that these tags have little effect on the native structure. This paper surveys and compares crystal structures with and without His tags. It is observed that actual refined tag residues fitted into density occur in less that 10% of the tagged sequences. However, higher resolution crystals are observed when this occurs. It is shown that these purification tags generally have no sign… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

6
158
0
2

Year Published

2011
2011
2019
2019

Publication Types

Select...
7
2
1

Relationship

0
10

Authors

Journals

citations
Cited by 197 publications
(167 citation statements)
references
References 18 publications
6
158
0
2
Order By: Relevance
“…The GH43B6, which fused with histidyl tag at the C-terminus, retained the enzymatic function indicated that histidyl tag did not interfere the function of GH43B6. The presence of the histidyl tag had no significant effect on protein structure (Carson et al 2007). Thus, biochemical characterization of GH43B6 could be conducted without cleaving of histidyl tag.…”
Section: Saccharoperbutylacetonicummentioning
confidence: 99%
“…The GH43B6, which fused with histidyl tag at the C-terminus, retained the enzymatic function indicated that histidyl tag did not interfere the function of GH43B6. The presence of the histidyl tag had no significant effect on protein structure (Carson et al 2007). Thus, biochemical characterization of GH43B6 could be conducted without cleaving of histidyl tag.…”
Section: Saccharoperbutylacetonicummentioning
confidence: 99%
“…However, no enzyme activity was detected when purified with NTA affinity column. This may be because His-tags generally have some minor effect on the structure of the native enzyme (Carson et al 2007). His-tags are known to mediate oligomerization via metal cation and can interact with some metal ions (Ca 2+, Mg 2+ ), which may affect the enzyme activity.…”
Section: Expression and Purification Of The Recombinant Enzymementioning
confidence: 99%
“…It has been shown that, in such a case, the His-tag does not interfere with the native protein structure. 28 The two molecules in the asymmetric unit of Nii4-WT were located side-by-side in identical orientations without any rotation. From the gel-filtration analysis, the molecular weight of the Nii4-WT was estimated to be 61.8 kDa.…”
Section: Structure Analysismentioning
confidence: 99%